Positive Solutions for Some Nonlocal and Nonvariational Elliptic Systems - Ubilla-Lopez, P (Taylor and Francis Ltd., 2016)
Using fixed point techniques, we study the existence and multiplicity of positive radial solutions for two classes of nonlocal elliptic systems defined on bounded annular domains or exterior domains. To this end, we reduce our problem to second-order functional ordinary elliptic systems. Our approach also allows us to study systems involving various orders, which serve as models for the suspension bridge equations. © 2015 Taylor & Francis.